PERBEDAAN PENGARUH SENAM LING TIEN KUNG DAN SENAM ERGONOMIK TERHADAP PENURUNAN KADAR ASAM URAT PADA LANSIA - Palupi, Lingling Marinda; Widiani, Esti (HOSPITAL MAJAPAHIT (JURNAL ILMIAH KESEHATAN POLITEKNIK KESEHATAN MAJAPAHIT), 2019)
Elderly people experience an aging process that causes organ weakness, physical deterioration, the emergence of various diseases, for example an increase in uric acid levels which can cause kidney stones, gout, and rheumatism. There needs to be efforts that are care, treatment, healthy lifestyle, and physical activities to maintain the health of the elderly. Some activities that can be done by the elderly include ergonomic gymnastics and Ling Tien Kung gymnastics. The purpose of this study was to compare the effect of ergonomic gymnastics and Ling Tien Kung's gymnastic influence on decreasing uric acid levels in the elderly. The researcher used a quasi-experimental research design with pre-test and post-test two groups. Each group was observed for uric acid levels before intervention, after intervention 4 times, and after intervention 8 times. Interventions were given twice a week for 4 weeks, with interventions at each meeting of 30-45 minutes. This study involved 14 respondents divided into 2 groups. The sampling technique of respondent selection was nonprobability sampling with purposive sampling method. Processing data used repeated ANOVA statistical tests. The Ling Tien Kung group had different results between the pre-test and post-test, but there is no difference between the med-pre-test. Ergonomic group had different results between pre-test and med-test and post-test, but there was no difference in results between med-test and post-test. Independent T-Test statistical test showed that between the two groups there were no differences in results, so it could be concluded that the two groups had the same effective resultsKeywords: Ling Tien Kung, ergonomics, gout, elderly